Falošné lieky - ako ich odhaliť? - Patlevič, Peter; Dorko, František; Švorc, Pavol; Vašková, Janka; Vaško, Ladislav (Chemické listy, 2013)
False drugs are unsafe products that are manufactured using incorrect, inactive, or harmful ingredients. These drugs are packaged and labeled to look like real trademark generic drugs to deceive the consumer. Chemical analysis is a crucial step in distinguishing original pharmaceutics and fakes. HPLC and MS analyses are standard methods for identification and quantitation of active ingredients and impurities. Thus they are often used to corroborate the results of less sophisticated methods such as colorimetry, TLC, GS, Raman, NIR, FTIR and NMR spectrometries. The analytical methods should be employed in forensic laboratories.
Keywords: artemisininy; Drug Contamination; inhibitory fosfodiesteras; Spectroscopy, Fourier Transform Infrared; chromatografie plynová; vysokoúčinná kapalinová chromatografie; Spectrum Analysis, Raman; Ramanova spektroskopie; Counterfeit Drugs; magnetická rezonanční spektroskopie; Chemistry Techniques, Analytical; padělané léky; Magnetic Resonance Spectroscopy; Mass Spectrometry; Phosphodiesterase Inhibitors; Chromatography, High Pressure Liquid; Drug Industry; Chromatography, Gas; chromatografie na tenké vrstvě; lidé; Artemisinins; chemické techniky analytické; Humans; kolorimetrie; kontaminace léku; hmotnostní spektrometrie; farmaceutický průmysl; Chromatography, Thin Layer; spektroskopie infračervená s Fourierovou transformací; Colorimetry